Solving the Fornberg–Whitham Model Derived from Gilson–Pickering Equations by Analytical Methods - Donal O’Regan; Safoura Rezaei Aderyani; Reza Saadati; Tofigh Allahviranloo (Axioms, 2024)
This paper focuses on obtaining traveling wave solutions of the Fornberg–Whitham model derived from Gilson–Pickering equations, which describe the prorogation of waves in crystal lattice theory and plasma physics by some analytical techniques, i.e., the exp-function method (EFM), the multi-exp function method (MEFM) and the multi hyperbolic tangent method (MHTM). We analyze and compare them to show that MEFM is the optimum method.